Loss of Hif-2α Rescues the Hif-1α Deletion Phenotype of Neonatal Respiratory Distress In Mice - Saini, Yogesh (PLoS One, 2015)
Hypoxia is a state of decreased oxygen reaching the tissues of the body. During prenatal development, the fetus experiences localized occurrences of hypoxia that are essential for proper organogenesis and survival. The response to decreased oxygen availability is primarily regulated by hypoxia-inducible factors (HIFs), a family of transcription factors that modulate the expression of key genes involved in glycolysis, angiogenesis, and erythropoiesis. HIF-1α and HIF-2α, two key isoforms, are important in embryonic development, and likely are involved in lung morphogenesis. We have recently shown that the inducible loss of Hif-1α in lung epithelium starting at E4.5 leads to death within an hour of parturition, with symptoms similar to neonatal respiratory distress syndrome (RDS). In addition to Hif-1α, Hif-2α is also expressed in the developing lung, although the overlapping roles of Hif-1α and Hif-2α in this context are not fully understood. To further investigate the independent role of Hif-2α in lung epithelium and its ability to alter Hif-1α-mediated lung maturation, we generated two additional lung-specific inducible Hif-α knockout models (Hif-2α and Hif-1α+Hif-2α). The intrauterine loss of Hif-2α in the lungs does not lead to decreased viability or observable phenotypic changes in the lung. More interestingly, survivability observed after the loss of both Hif-1α and Hif-2α suggests that the loss of Hif-2α is capable of rescuing the neonatal RDS phenotype seen in Hif-1α-deficient pups. Microarray analyses of lung tissue from these three genotypes identified several factors, such as Scd1, Retlnγ, and Il-1r2, which are differentially regulated by the two HIF-α isoforms. Moreover, network analysis suggests that modulation of hormone-mediated, NF-κB, C/EBPα, and c-MYC signaling are central to HIF-mediated changes in lung development.